The constitution of India popular sovereignty and democratic transformations - Sen, Sarbani (New Delhi ; Oxford : Oxford University Press, 2010)
The relationship between constitutionalism and popular sovereignty in the Indian context is the critical focus of this original work in political theory, jurisprudence, and constitutionalism. This book examines fundamental issues about the basic law of the land, the author contending that it is necessary to go beyond viewing democracy merely as the vesting of fundamental authority in institutions of elected representatives.
Originally published: 2007.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Sept. 4, 2012).
Keywords: Constitutional law -- India; Constitutional history -- India